Ergonomic Analysis and Redesign of Bus Handgrips Using Rapid Upper Limb Assessment (RULA) and Posture Evaluation Index (PEI) - Veronika Chintia Dewi; Rifano Rifano; Gunawan Gunawan; Riza Phahlevi Marwanto (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study aims to analyze and improve the ergonomic performance of bus handgrips on Metro Jabar Trans using an integrated approach combining Rapid Upper Limb Assessment (RULA) and Posture Evaluation Index (PEI). The research employed a quantitative method involving 30 respondents, with data collected through observation, interviews, joint angle measurements, and anthropometric analysis. A virtual simulation was developed using Jack 8.4 software to evaluate ergonomic conditions based on RULA, Lower Back Analysis (LBA), and Ovako Working Posture Analysis System (OWAS), which were then integrated into the PEI metric. The results indicate that the existing handgrip design produces RULA scores predominantly at levels 5–6, reflecting moderate ergonomic risk, with PEI values ranging from 1.358 to 1.875, indicating suboptimal conditions. A redesigned handgrip was developed by optimizing key dimensions, including width, diameter, and finger clearance, based on anthropometric data. Simulation results demonstrate a consistent reduction in ergonomic risk, with PEI values decreasing to a range of 0.925 to 1.221. The reduction in PEI values, ranging from 0.233 to 0.903, confirms improved postural conditions and reduced risk of musculoskeletal disorders. These findings highlight that integrating posture assessment and quantitative ergonomic indices can effectively support the development of safer and more comfortable public transportation facilities.